A Study of Richard Swinburne's View on the Soul and the Probability of Life after Death - Seyyed Jaaber Mousavirad (حکمت اسرا)
Richard Swinburne holds that the life after death is possible only if human being has a soul that remains after death and preserves human identity. For this reason, he attempts to make life after death a possible and probable truth by proving the existence of soul. He considers objections such as "not explaining the quality of communication between two completely different essences", "not explaining the reason for the soul's relationship with a particular body" and "incompatibility with the principle of physical causal closure", and believes that the acceptance of soul does not face any intellectual or philosophical problems. After answering the problems of the theory of the soul, he endeavors to prove the existence of the soul on the basis of the following arguments: personal identity, consciousness, the simultaneous existence of mental states, and the argument from possibility. This article, while examining and criticizing some of Swinburne's arguments, defends some of the other arguments presented by him and, accordingly, shows the possibility of life after death.